2005
DOI: 10.1038/sj.ijo.0803113
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and physiological regulation of body fatness: a cross-sectional study in elderly men

Abstract: Objective: To identify the characteristics of physical activity that are the most correlated to total and truncal fatness and to physiological parameters involved in fat oxidation in elderly men. Design: Cross-sectional study. Subjects: A total of 25 healthy elderly men selected with a wide range of physical activity behavior (65.973.4 years). Measurements: Total and truncal fat masses (by dual-energy X-ray absorptiometry), time spent and energy expended (EE day ) at specific activity intensities (o40, 40-60, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The subjects stopped sport exercise 2 days before initial metabolic measurements that included basal indirect calorimetric measurement, muscle biopsy, 3‐h euglycemic–hyperinsulinemic clamp, and body composition determination. From two days before and throughout the metabolic measurements, the volunteers were placed on a controlled diet (35%, 50% and 15% of energy in the form of lipids, carbohydrates and proteins, respectively) [12]. Heart rate was re‐recorded over 7 days in free‐living conditions at the end of the training cessation period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects stopped sport exercise 2 days before initial metabolic measurements that included basal indirect calorimetric measurement, muscle biopsy, 3‐h euglycemic–hyperinsulinemic clamp, and body composition determination. From two days before and throughout the metabolic measurements, the volunteers were placed on a controlled diet (35%, 50% and 15% of energy in the form of lipids, carbohydrates and proteins, respectively) [12]. Heart rate was re‐recorded over 7 days in free‐living conditions at the end of the training cessation period.…”
Section: Methodsmentioning
confidence: 99%
“…The tests were all performed on the same cycloergometer (Ergomeca, Monark, Sweden) under cardiovascular supervision by a cardiologist, as described in [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of cross-sectional (Aubertin-Leheudre et al 2006;Baumgartner et al 1998;Melton et al 2000;Rimbert et al 2006;Starling et al 1999;Szulc et al 2004) and longitudinal studies (Hughes et al 2001;Rantanen et al 1997) have shown relationships between low levels of habitual physical activity and the presence or the development of sarcopenia. However, one limitation in most of these studies (Baumgartner et al 1998;Hughes et al 2001;Melton et al 2000;Rantanen et al 1997;Rimbert et al 2006;Szulc et al 2004) was that physical activity patterns were assessed by questionnaires; commonly, inquiry was made Communicated by Roberto Bottinelli.…”
Section: Introductionmentioning
confidence: 95%
“…However, one limitation in most of these studies (Baumgartner et al 1998;Hughes et al 2001;Melton et al 2000;Rantanen et al 1997;Rimbert et al 2006;Szulc et al 2004) was that physical activity patterns were assessed by questionnaires; commonly, inquiry was made Communicated by Roberto Bottinelli.…”
Section: Introductionmentioning
confidence: 99%